KONTRIBUSI FILSAFAT MORAL DALAM MENINGKATKAN KARAKTER KINERJA PADA MAHASISWA DENGAN STATUS PEKERJA - Irianto; zaldy dzulkhadavid; Anita Sardewi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2023)
By thinking philosophically, an individual can overcome various complexities in his life. This can happen if an individual understands what philosophy is, because by applying philosophical thinking in every aspect of life, various problems that arise in life can be resolved well and wisely. Philosophy itself can be interpreted lexically as a view or way of life. If every Indonesian wants to do philosophy, that is, make philosophy a way of life, regardless of their daily profession, then philosophical knowledge can be used to perfect their lives, including in forming their performance character. Because the consequences of a philosophical view are significant and determine a person's attitude toward himself, other people, the world, and God. This research aims to describe how moral philosophy can be applied in shaping the performance character of students with employment status. The research was carried out using qualitative methods like library research which used books and other literature as objects. The results of the research are that the symptoms of weakness and the negative impacts of studying while working can be minimized or even eliminated if an individual can position himself as a moral philosopher who can find answers to the value of belief for his character and life. This kind of pattern will greatly contribute to the quality of student life in the current period and the future, this is because the construction of philosophical thinking can reduce negative fluctuations in life which is always dynamic and fluctuating